Immune senescence: significance of the stromal microenvironment. (23rd September 2016) - Masters, A. R.; Haynes, L.; Su, D.‐M.; Palmer, D. B.
Summary: The immune system undergoes age‐associated changes known as immunosenescence, resulting in increased susceptibility to infections, cancers and autoimmunity in the aged. The basis of our understanding of immunosenescence has been derived primarily from studies examining intrinsic defects within many of the cells of the immune system. While these studies have provided insight into the mechanisms of immunosenescence, a picture is now emerging that the stromal microenvironment within lymphoid organs also contributes significantly to the age‐associated decline of immune function. These extrinsic defects appear to impact the functional activity of immune cells and may offer a potential target to recover immune activity. Indeed, rejuvenation studies which have targeted the stromal niche have restored immune function in aged successfully, highlighting the impact of the microenvironment towards the aetiology of immunosenescence. Abstract : Whilst the exact mechanisms underlying immunosenescence are still unclear, several studies have identified intrinsic defects within many of the cells of the immune system. Despite the stromal niche playing a critical role in the development, maintenance and activation of immune cells the role of the microenvironment in immunosenescence remains an overlook area, but is increasingly becoming recognised as playing an important role in the decline of immune function in the aged.